2023
DOI: 10.1111/tid.14183
|View full text |Cite
|
Sign up to set email alerts
|

Slaying the “Troll of Transplantation”—new frontiers in cytomegalovirus management: A report from the CMV International Symposium 2023

Camille N. Kotton,
Julian Torre‐Cisneros,
Ibrahim Yakoub‐Agha

Abstract: The 2023 International CMV Symposium took place in Barcelona in May 2023. During the 2‐day meeting, delegates and faculty discussed the ongoing challenge of managing the risk of cytomegalovirus infection (the Troll of Transplantation) after solid organ or hematopoietic cell transplantation. Opportunities to improve outcomes of transplant recipients by applying advances in antiviral prophylaxis or pre‐emptive therapy, immunotherapy, and monitoring of cell‐mediated immunity to routine clinical practice were deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…CMV prophylaxis refers to the use of antivirals in all patients at increased risk of CMV reactivation, whereas preemptive therapy refers to the administration of antivirals only with evidence of CMV replication. The optimal approach to the prevention and treatment of infection due to CMV remains uncertain despite years of experience with antiviral therapies, due to the dynamic immune status specific to CMV [ 1 , 3 , 33 ]. A recent worldwide survey on CMV prevention strategies in SOT found that universal prophylaxis was used in 90% of centers in D+/R− and in 50% in of R+ SOT with variable duration depending on the type of transplant, CMV serostatus, and induction immunosuppression [ 4 ▪▪ ].…”
Section: Prophylaxis Versus Pre-emptive Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV prophylaxis refers to the use of antivirals in all patients at increased risk of CMV reactivation, whereas preemptive therapy refers to the administration of antivirals only with evidence of CMV replication. The optimal approach to the prevention and treatment of infection due to CMV remains uncertain despite years of experience with antiviral therapies, due to the dynamic immune status specific to CMV [ 1 , 3 , 33 ]. A recent worldwide survey on CMV prevention strategies in SOT found that universal prophylaxis was used in 90% of centers in D+/R− and in 50% in of R+ SOT with variable duration depending on the type of transplant, CMV serostatus, and induction immunosuppression [ 4 ▪▪ ].…”
Section: Prophylaxis Versus Pre-emptive Treatmentmentioning
confidence: 99%
“…Moreover, it may increase the cost of transplantation, and negatively impact SOT quality of life [ 1 , 2 ▪▪ ]. However, there are still several unmet needs in CMV management in posttransplant settings [ 3 ]. In the present paper we will review the most recent advances in prevention and treatment of CMV diseases in SOT recipients.…”
Section: Introductionmentioning
confidence: 99%